Antinociceptive and neuropharmacological activities of methanol extract of Phoenix sylvestris fruit pulp - Shajib, Md. Shafiullah (Front Pharmacol, 2015)
Fruits of Phoenix sylvestris Roxb. (Arecaceae) are used to treat back pain, toothache, headache, arthritis, nervous debility and as sedative. The aim of this study was to evaluate the antinociceptive and neuropharmacological activities of methanol extract of P. sylvestris fruit pulp (MEPS). The antinociceptive activity of MEPS was evaluated by heat-induced (hot plate, tail immersion test) and chemical-induced pain models (acetic acid-induced writhing, formalin-induced nociception, glutamate-induced nociception and paw edema test). The effect of MEPS on central nervous system (CNS) was studied using hole cross test, open field test, sodium thiopental-induced sleeping time and elevated plus maze test. MEPS showed strong, significant and dose-dependent antinociceptive activity in all heat-induced and chemical-induced pain models at all experimental doses. Involvement of opioid receptor mediated analgesia was evident from the reversal of analgesic effect by naloxone. MEPS also showed reduced locomotor activity in both hole cross and open field tests. The increase in sleeping time in sodium thiopental-induced sleeping test and anxiolytic activity in elevated plus maze test were also significant. So, it is evident that MEPS possesses strong central and peripheral antinociceptive activity as well as CNS depressant, sedative and anxiolytic activity. The results justify the ethnomedicinal use of P. sylvestris fruit in different painful conditions and CNS disorders.